Evaluasi Akuntansi Pertanggungjawaban sebagai Alat Bantu Manajemen dalam Pengendalian Biaya : Studi Kasus pada PT. Cahaya Buana Intitama - Pamungkas, Bambang; Afrianti, Vera (Jurnal Ilmiah Ranggagading (JIR), 2006)
This research was conducted to find out the implementation of responsibility accounting in controlling cost. It tried to measure and evaluate the plan and activity of management at the firm by determining income and cost for department or division that must be responsible. The report of responsibility every month and then yearly report. Cahaya Buana Intitama, Inc. has determined standard cost from the budget to make easier in evaluating cost centre efficiency, besides to analyze deviation in term of the real cost is smaller than standard cost. Therefore, the deviation is advantageous and it mean that cost centre is able to work efficiently, and so it reverse. Keywords: Responsibility Accounting; Cost Control